ASEAN+3 or ASEAN+6: Which way forward? - Masahiro Kawai; Ganeshan Wignaraja (Asian Development Bank Institute (ADBI), 2007)
The surge in free trade agreements (FTAs) in East Asia since the Asian financial crisis has prompted a lively debate on the characteristics, impact, and future path of FTAs in the region. To inform the ongoing debate, this paper maps the salient characteristics of East Asian FTAs using a new FTA database, identifies several key issues to be addressed, and explores economic effects using computable general equilibrium (CGE) analysis. The paper suggests that WTO-plus elements need to be further expanded and the negative aspects of FTAs be minimized. The paper argues that consolidation of multiple and overlapping FTAs into a single East Asian FTA can help mitigate the harmful 'noodle bowl' effects of different rules of origin (ROOs) and standards and that the consolidation at the ASEAN+6 level would yield the largest gains to East Asia among plausible regional trade arrangements-while the losses to non-members would be relatively small. For such consolidation to occur, ASEAN must act as the regional 'hub' by further deepening ASEAN economic integration, the plus-three countries (PRC, Japan, and Korea) need to collaborate more closely, and India needs to pursue further structural reforms. Furthermore, substantial international support is required to strengthen the supply-side capacity of poorer ASEAN countries-including the building of trade-supporting infrastructure (transport, energy, and telecommunications)-so that they can take advantage of integrated regional markets and narrow development gaps within ASEAN. Over time, it would be desirable for East Asia to strengthen economic ties with North America and Europe by connecting an ASEAN+6 FTA with NAFTA and the EU.
Keywords: F15; F17; O24; 330; Handelsregionalismus; Freihandelszone; Außenwirtschaftspolitik; Simulation; Allgemeines Gleichgewicht; ASEAN-Staaten; Ostasien